Anisotropic Disturbance Rejection for Kinematically Redundant Systems With Applications on an UVMS - Marais, Wilhelm J.; Williams, Stefan B.; Pizarro, Oscar (IEEE robotics and automation letters, 2021)
Systems with a manipulator and a mobile base, such as in aerial and underwater applications, are susceptible to disturbances which create difficulties in maintaining a desired end effector pose. However, kinematically redundant vehicle manipulator systems can make use of the continuous space of configurations to solve an inverse kinematics problem that can be exploited to improve disturbance rejection. In this letter, we explore disturbance rejection along a given direction for both a single pose, and along a trajectory. Simulated validation results are provided on an underwater vehicle manipulator system subject to environmental disturbances.